ANALISIS HUKUM ADMINISTRASI PERIZINAN USAHA: STUDI KASUS PENYEGELAN GERAI MIE GACOAN DI KOTA BOGOR - Ni Made Yuyeni Gita Sari; I Made Arjaya (Faculty of Law-Universitas Bandar Lampung, 2025)
Licensing is an essential instrument for business actors in developing industrial enterprises, serving as a guideline to ensure a rational legal foundation (a means of legal protection). Licensing is closely related to industrial development, as stipulated in Law No. 3 of 2014 concerning Industry. If an industrial business does not meet the licensing requirements, it may have a negative impact on the continuity of its business operations. One notable example can be seen in several cases of business closures in the food industry, one of which involves Mie Gacoan—a brand that has gained immense popularity among teenagers and adults. However, the business has not yet fulfilled the required licensing conditions in accordance with applicable regulations. The establishment of Mie Gacoan outlets without meeting proper construction and operational licensing requirements has led to various impacts on both the social and environmental surroundings. The purpose of this journal study is to examine the granting of industrial business development licenses, to identify licensing issues surrounding Mie Gacoan in several regions of Indonesia, to analyze the impacts resulting from its establishment, and to assess the overall feasibility of the business. The research method used in this study is a literature review method, which includes data sources, data collection, data analysis, and the author’s analytical discussion.